Corporate Risk Management and the Incentive Effects of Debt - CAMPBELL, TIM S.; KRACAW, WILLIAM A. (Journal of Finance, 1990)
ABSTRACT This paper demonstrates how the incentive of manager‐equityholders to substitute toward riskier assets, commonly referred to as the “asset substitution problem,” is related to the level of observable risk in the firm. When observable and unobservable risks are sufficiently positively correlated, increases (decreases) in observable risk generate the incentive for manager‐equityholders to increase (decrease) unobservable risk. Thus, credible commitments to hedge observable risk can benefit the firm's manager‐equityholders by reducing the incentive to shift risk and the associated agency cost of debt. This provides a positive rationale for hedging diversifiable risk at the firm level.